2016
DOI: 10.1111/1750-3841.13342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Salts on Physical and Mechanical Properties of Pea Starch Films

Abstract: To identify the significant contribution of intermolecular hydrogen bonds of starch molecules to the film structure formation, pH of film-forming solutions was adjusted and also various salts (NaCl, CaCl2 , CaSO4 , and K2 SO4 ) were mixed into the glycerol-plasticized pea starch film. The film made from pH 7 possessed the highest tensile strength-at-break (2 times) and elastic modulus (4 to 15 times) and the lowest elongation-at-break compared with those of the films made from acid and alkali environments. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The results show that the LRS/KGM mixture had a lower peak viscosity, final viscosity, setback viscosity, pasting time, peak time, and a higher breakdown viscosity in acidic conditions than in a neutral environment. Given that acid hydrolysis destroys glycosidic bonds in molecules [22], the complete pasting of starch molecules in acidic conditions requires less energy and therefore LRS is gelatinized faster and at lower temperatures. The hydrolysis of the LRS/KGM mixture in acidic environments is irreversible and influences the rearrangement of starch molecules upon temperature reduction, accompanied by a decrease in the retrogradation rate and value.…”
Section: Results and Analysismentioning
confidence: 99%
“…The results show that the LRS/KGM mixture had a lower peak viscosity, final viscosity, setback viscosity, pasting time, peak time, and a higher breakdown viscosity in acidic conditions than in a neutral environment. Given that acid hydrolysis destroys glycosidic bonds in molecules [22], the complete pasting of starch molecules in acidic conditions requires less energy and therefore LRS is gelatinized faster and at lower temperatures. The hydrolysis of the LRS/KGM mixture in acidic environments is irreversible and influences the rearrangement of starch molecules upon temperature reduction, accompanied by a decrease in the retrogradation rate and value.…”
Section: Results and Analysismentioning
confidence: 99%
“…The reason could be low pea flour and HPMC concentration leading no branching of nanofibres. Edible films of pea protein isolate and pea starch gave 8.4 9 10 À14 kg m À1 s À1 Pa À1 (Kowalczyk & Baraniak, 2011) and 7.3 9 10 À13 kg m À1 s À1 Pa À1 (Choi et al, 2016), respectively. The branching was attributed to uneven distribution of the charge carried by the jets, which was caused by jet elongation and solvent evaporation.…”
Section: Characterisation Of Nanofibresmentioning
confidence: 98%
“…In this current study, WVP values of fibres varied in 12.18-17.54 9 10 À16 kg m À1 s À1 Pa À1 which was lower compared to edible films in literature. Edible films of pea protein isolate and pea starch gave 8.4 9 10 À14 kg m À1 s À1 Pa À1 (Kowalczyk & Baraniak, 2011) and 7.3 9 10 À13 kg m À1 s À1 Pa À1 (Choi et al, 2016), respectively. This showed that combining pea flour with HPMC and PEO is an advantage in food packaging area in terms of reduction in WVP values.…”
Section: Characterisation Of Nanofibresmentioning
confidence: 98%
“…Other strategies, including chemical modifications (e.g., oxidation or hydroxypropylation) (Lafargue et al., 2007; Wu et al., 2010), incorporation of hydrophobic compounds (e.g., beeswax) (Han et al., 2006), altering pH (Choi et al., 2016), and adding salts (e.g., NaCl) (Choi et al., 2016), have also been developed to produce starch‐based films with enhanced mechanical and barrier properties. In addition, different types of fillers, such as starch nanocrystals and cellulose nano‐whiskers, can reinforce the microstructure of starch films and create a torturous path for water molecules to penetrate, which therefore improves the mechanical and barrier properties of the final film products (Cano, Fortunati, Cháfer, & González‐Martínez et al., 2015; Chen et al., 2009; Farrag et al., 2018; Li, Qiu et al., 2015).…”
Section: Industrial Applications Of Pulse Starchesmentioning
confidence: 99%